2019
DOI: 10.1016/j.quascirev.2019.105995
|View full text |Cite
|
Sign up to set email alerts
|

Risk and reward: Explosive eruptions and obsidian lithic resource at Nabro volcano (Eritrea)

Abstract: Compared with other manifestations of climate variability that may not be perceived within a human lifetime, abrupt environmental disturbances arising from volcanism can be directly experienced. Despite abundant Pleistocene calderas in the East African Rift and Afar, and the significance of regional tephra horizons for archaeological and paleoenvironmental dating, the entanglements of volcanoes and their eruptions with human behaviour and paleoecology have received little attention. Here, we focus on the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Indeed, from eastern to western Africa, understanding the nature of the relationship between the MSA and LSA remains incomplete, with little consensus on issues ranging from timing to geography to technology. Understanding the temporal and spatial variation in technologies (51)(52)(53), subsistence (54), mobility (55,56), and potential ecosystem modifications (57) of Middle and Late Pleistocene human populations is best accomplished via comprehensive research on stratified, calibrated sequences of timesuccessive, geographically limited archaeological occurrences associated with skeletal remains. The rapidly expanding nexus of MSA localities in the Afar thereby creates additional opportunities for progress in testing the modes and tempos of biological and cultural change and the causes of observed variation (58)(59)(60)(61).…”
Section: Broader Implications and Potentialsmentioning
confidence: 99%
“…Indeed, from eastern to western Africa, understanding the nature of the relationship between the MSA and LSA remains incomplete, with little consensus on issues ranging from timing to geography to technology. Understanding the temporal and spatial variation in technologies (51)(52)(53), subsistence (54), mobility (55,56), and potential ecosystem modifications (57) of Middle and Late Pleistocene human populations is best accomplished via comprehensive research on stratified, calibrated sequences of timesuccessive, geographically limited archaeological occurrences associated with skeletal remains. The rapidly expanding nexus of MSA localities in the Afar thereby creates additional opportunities for progress in testing the modes and tempos of biological and cultural change and the causes of observed variation (58)(59)(60)(61).…”
Section: Broader Implications and Potentialsmentioning
confidence: 99%
“…It has been argued that mobility associated with herding may have supported its spread, both through interaction and exchange of livestock with foragers, and through social networks that enabled them to thrive faced with growing aridity (Marshall et al 2011). It has also been suggested that maritime mobility across the Red Sea, confirmed through obsidian sourcing studies , Oppenheimer et al 2019) may have played a role in the spread of herding by means of coastal fisher-herding communities from southern Arabia (Gutherz et al 2017;. However, the current study provides new data that suggest traditions in the Abhe Lake basin had few to no parallels with those in surrounding regions across the three periods of settlement documented in the region.…”
Section: Africamentioning
confidence: 54%
“…1a). These are large stratovolcanoes that produced caldera-forming explosive eruptions (Barberi et al 1974a;Wiart and Oppenheimer 2005;Oppenheimer et al 2019) and lava flows generally more alkaline with respect to the tholeiitic-transitional axial volcanism (Civetta et al 1975;De Fino et al 1978;Donovan et al 2018). The most recent eruption of a marginal volcano was in 2011 at Nabro, which produced basaltic to basaltic trachyandesite tephra and lava (Hamlyn et al 2018;Donovan et al 2018).…”
Section: The Afar Depressionmentioning
confidence: 99%